Treatment outcomes of young patients with invasive breast cancer treated radically at Groote Schuur Hospital from 2013-2017: A single centre study - Tangane, Gomolemo (Division of Radiology, 2023)
Treatment outcomes of young patients with invasive breast cancer treated radically at Groote Schuur Hospital from 2013 to 2017: A single centre study Background: Breast cancer is the leading cause of cancer- related deaths globally, and the commonest cancer in women under 40 years. There is currently a lack of data relating to treatment outcomes of young women with breast cancer particularly in low-and middle-income countries. Aim: This study aims to evaluate the treatment outcomes of young patients (under 40 years) treated radically for invasive breast cancer in a low-and middle-income setting. Settings: Groote Schuur Hospital, Cape Town, South Africa Methods: A retrospective review of 101 women under 40 years, with invasive breast cancer treated radically, between 2013 and 2017 was conducted. Patient characteristics, tumour characteristics, disease stage, treatment, and follow-up were recorded. Primary objectives included evaluating overall and disease free survival, and analysing recurrence patterns and clinicopathological features. Results: The five-year overall and disease free survival for the entire cohort was 77% and 51%, respectively. Five-year overall survival by molecular subtype showed that Luminal A had the best survival, while triple negative breast cancer had the worst overall survival. Conclusion: Young women with breast cancer have poor survival outcomes despite early presentation. There is limited data regarding breast cancer treatment outcomes in patients under forty years.